Arabidopsis Myosin XI-K Localizes to the Motile Endomembrane Vesicles Associated with F-actin - Peremyslov, Valera V.; Klocko, Amy L.; Fowler, John E.; Dolja, Valerian V. (Frontiers in Plant Science, 2012)
Plant myosins XI were implicated in cell growth, F-actin organization, and organelle transport, with myosin XI-K being a critical contributor to each of these processes. However, subcellular localization of myosins and the identity of their principal cargoes remain poorly understood. Here, we generated a functionally competent, fluorescent protein-tagged, myosin XI-K, and investigated its spatial distribution within Arabidopsis cells. This myosin was found to associate primarily not with larger organelles (e.g., Golgi) as was broadly assumed, but with endomembrane vesicles trafficking along F-actin. Subcellular localization and fractionation experiments indicated that the nature of myosin-associated vesicles is organ- and cell type-specific. In leaves, a large proportion of these vesicles aligned and co-fractionated with a motile endoplasmic reticulum (ER) subdomain. In roots, non-ER vesicles were a dominant myosin cargo. Myosin XI-K showed a striking polar localization at the tips of growing, but not mature, root hairs. These results strongly suggest that a major mechanism whereby myosins contribute to plant cell physiology is vesicle transport, and that this activity can be regulated depending on the growth phase of a cell.